Overlapping and CpG methylation-sensitive protein-DNA interactions at the histone H4 transcriptional cell cycle domain: distinctions between two human H4 gene promoters. - van Wijnen, A J (1992)
Transcriptional regulation of vertebrate histone genes during the cell cycle is mediated by several factors interacting with a series of cis-acting elements located in the 5' regions of these genes. The arrangement of these promoter elements is different for each gene. However, most histone H4 gene promoters contain a highly conserved sequence immediately upstream of the TATA box (H4 subtype consensus sequence), and this region in the human H4 gene FO108 is involved in cell cycle control. The sequence-specific interaction of nuclear factor HiNF-D with this key proximal promoter element of the H4-FO108 gene is cell cycle regulated in normal diploid cells (J. Holthuis, T.A. Owen, A.J. van Wijnen, K.L. Wright, A. Ramsey-Ewing, M.B. Kennedy, R. Carter, S.C. Cosenza, K.J. Soprano, J.B. Lian, J.L. Stein, and G.S. Stein, Science, 247:1454-1457, 1990). Here, we show that this region of the H4-FO108 gene represents a composite protein-DNA interaction domain for several distinct sequence-specific DNA-binding activities, including HiNF-D, HiNF-M, and HiNF-P. Factor HiNF-P is similar to H4TF-2, a DNA-binding activity that is not cell cycle regulated and that interacts with the analogous region of the H4 gene H4.A (F. LaBella and N. Heintz, Mol. Cell. Biol. 11:5825-5831, 1991). The H4.A gene fails to interact with factors HiNF-M and HiNF-D owing to two independent sets of specific nucleotide variants, indicating differences in protein-DNA interactions between these H4 genes. Cytosine methylation of a highly conserved CpG dinucleotide interferes with binding of HiNF-P/H4TF-2 to both the H4-FO108 and H4.A promoters, but no effect is observed for either HiNF-M or HiNF-D binding to the H4-FO108 gene. Thus, strong evolutionary conservation of the H4 consensus sequence may be related to combinatorial interactions involving overlapping and interdigitated recognition nucleotides for several proteins, whose activities are regulated independently. Our results also suggest molecular complexity in the transcriptional regulation of distinct human H4 genes.